Peran Influencer Marketing Terhadap Minat Beli Konsumen Generasi Z di Indonesia - Fitri, Rati Saktia (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to identify the role of influencer marketing on the purchasing intentions of Generation Z (Gen Z) consumers in Indonesia and the most influential factors in shaping their purchasing decisions. Using a Systematic Literature Review (SLR) approach, this study analyzed various empirical studies relevant to the topic of influencer marketing and Gen Z consumer behavior. The results indicate that influencer marketing consistently shows a positive influence on Gen Z purchasing intention and purchasing decisions. The most dominant factors influencing purchasing decisions are brand image, product quality, influencer credibility, and marketing content. The mechanism of influence occurs through influencer credibility, the strength of reviews/ testimonials, and social interactions on digital platforms, with TikTok and Instagram being the most effective platforms. The findings indicate that non-celebrity influencers are more effective than celebrity influencers because they are perceived as more authentic and relatable. This study also identifies methodological limitations and substantive gaps in previous studies and provides practical implications for digital marketers and business practitioners in designing effective influencer marketing strategies to reach the Gen Z segment in Indonesia.